Social protection measures as determinants of food [in]security in households of public school students during the covid-19 pandemic (Revista Contexto & Saúde, 2026)
The objective of this study was to evaluate the association between the co-occurrence of social protection measures and food insecurity in households of public school students from two municipalities in Minas Gerais. This was a cross-sectional study, conducted through telephone interviews in June/July 2020, with household heads of students enrolled in basic education in the municipalities of Ouro Preto and Mariana, Minas Gerais, Brazil. Data on the receipt of social protection measures were collected: Bolsa Família, Emergency Aid, and access to government food baskets. Food insecurity (FI) was assessed using the Brazilian Food Insecurity Scale. Descriptive analyses, Pearson’s Chi-square test, and univariate and multivariate logistic regression were performed, adjusting for household head’s educational level and type of street pavement. Among the 542 households evaluated, 82.0% were in a situation of food insecurity, 63.0% received Emergency Aid, and 23.0% received all three social protection measures. Households receiving two and three social protection measures were 2.05 (95% CI: 1.01–4.15) and 2.85 (95% CI: 1.31–6.16) times more likely to experience food insecurity, respectively, compared to those receiving none. These findings indicate that families experiencing food insecurity were reached by social protection policies and measures; however, these measures were not sufficient to ensure the Human Right to Adequate Food and Food and Nutrition Security.
Keywords: Social distancing; Food security; Hunger; Social protection